Misidentifying an innocent suspect can alter witness recollections of the perpetrator’s face - Eisen, Mitchell (Psychology, crime & law, 2023)
Two experiments were conducted to examine whether misidentifying an innocent suspect with a unique feature (i.e. facial tattoo) would impact witnesses’ recollections of the culprit so that they would mistakenly describe the culprit as having that same feature, when in reality, he did not. In both experiments, participants viewed a video of a simulated carjacking in which the perpetrator’s face was visible from a close or far distance, and were then led to misidentify an innocent suspect from a suggestive culprit-absent photo-array. The innocent suspect either had a tattoo photoshopped onto his face, or, like the culprit, had no visible facial markings. After making the identification, half the participants received confirming post-identification feedback. Finally, participant-witnesses were asked to describe the culprit in their own words. In both experiments, over a third of the participant-witnesses in the tattoo condition mistakenly described the culprit as having had a tattoo on his face. In Experiment 2, remember/know judgements indicated that participant/witnesses in the tattoo condition were also more likely to report remembering that the culprit had a face tattoo, rather than simply knowing this to be true. Also, as predicted, in both experiments, confirming feedback significantly boosted erroneous reports of recalling the tattoo.